Autonomy and informed consent. Models of the relationship between the physician and the mentally sick. - Sala, Roberta (Medicina e Morale, 1994)
The study analyses the difficult relationship between the physician and the psychiatric patient in the light of this century's generai medical crisis. After describing the 20th century philosophical criticism of the concept of science and after illustrating the difficulties with traditional models of medicine (e.g. paternalistic, contractual), the author takes into consideration the various ways of understanding mental diseases and the relationship between the physician and the psychiatric patient with particular reference to the communication of the truth to the psychiatric patient and to the problems regarding informed consent.